Simulation and Prediction of Zhuzhou Urban Wetland Landscape Pattern Based on LCM Model - Wen Zhan, Huifeng Cheng and Shouyun Shen (Nature Environment and Pollution Technology, 2021)
The urban wetland is a precious wealth of the city, which has a very important role and value for the development of human and society. Zhuzhou is a traditional industrial city in China, which is located in the lower reaches of the Xiangjiang River and rich in urban wetland resources. In order to protect, utilize and manage urban wetland resources scientifically, based on LCM model platform, using Landsat series remote sensing images and other data, this paper systematically analyses the land use change process of Zhuzhou urban wetland from 2006 to 2016 and simulates and forecasts the urban wetland landscape pattern in 2021. The prediction results show that the urban wetland in Zhuzhou city will change continuously in 2021, but the overall change is relatively small, which is basically consistent with the change trend and regain of urban wetland in 2006~2016. Among them, the change of paddy fields area is the largest, with a total decrease of 1364.8ha; the increase of reservoirs area is 82.4ha; the decrease of pond area is 34.6ha, while riverine wetland is basically unchanged. In addition, Zhuzhou urban wetland landscape pattern change is affected by both natural and human factors, while human activities have a more significant impact on the wetland, with both positive and negative effects.